METHODICAL PROVISION OF CRISIS DIAGNOSIS OF DOMESTIC ENTERPRISES - Rudyk, O. R. (Science and Transport Progress, 2007)
The article is devoted to classification of methods of diagnostics in the process of anti-crisis management by enterprises. Kinds and basic stages of diagnostics and monitoring of the financial state of enterprise are considered.